Khalil's Methodology of Preference in his Summary Al-Mukhtasar (مجلة الواحات للبحوث والدراسات, 2026)
Khalil's Summary, “Al-Mukhtasar”, stands out from other jurisprudential summaries for its unique approach to addressing jurisprudential branches and issues. This approach addresses jurisprudential differences within the doctrine, establishes the basis for Fatwas, and explains the most likely, most Popular, and most Authoritative Opinions. This entails a precision, editing, and investigation that distinguishes the book and has become a standard practice adopted by most Maliki Scholars after its inception. This study, entitled “Khalil's Methodology of Preference in his Summary Al-Mukhtasar”, aims to demonstrate the methodology of preference adopted by Imam Khalil Ibn Ishaq in his “Mukhtasar”, along with an explanation of his terminology and methods of preference. He follows an inductive analytical approach by tracing the most important commentaries and annotations written on Al-Mukhtasar, analyzing the imam's decisions on this matter, and arriving at the features of the methodology of preference in Khalil's Mukhtasar. He has special terms for preference, selection, presentation, and deduction, when there is disagreement over branches of the doctrine. He has three approaches to this: the method of preference, the method of silence and contentment with conveying the disagreement, and the method of not preferring due to lack of justification.